The clinical features and prognosis of scan negative uro-neurological disorders. Issue 6 (27th May 2022) - Hoeritzauer, Ingrid; Carson, Alan; Statham, Patrick; Panicker, Jalesh; Granitsiotis, Voula; Eugenicos, Maria; Summers, David; Demetriades, Andreas; Stone, Jon
Abstract : Background: More than 50% of patients presenting with cauda equina syndrome (CES) have normal imaging. These patients require phenotyping to ascertain symptom aetiology and mechanism. Prospective Study Results: 198 patients presented with suspected CES over 28 months. 47 were diagnosed with 'scan-positive' CES (mean age 48yrs, 43% female). 76 patients had evidence of nerve root compres- sion or displacement and were placed into a 'mixed' category (mean age 46yrs, 71% female) and 61 patients had normal scans 'scan-negative' CES (mean age 40yrs, 77% female). Fourteen patients had a neurological diagnosis explaining their clinical CES symptoms during admission. Patients with 'scan-positive' CES were more likely to have reduced or lost bilateral ankle jerks (78% vs. 30% and 12%, p≤0.0001). Patients with 'scan-negative' CES were found to have positive signs of a functional neurological disorder on examination (11% v. 34% and 68%, p≤0.0001) as well as high rates of panic, medication usage and psychopathology. Four patients out of 151 (4%, mixed group n=3, 'scan-negative' group n=1) had a neurological diagnosis after discharged which potentially explained their clinical CES presentation. Conclusions: This is the first well phenotyped, prospective study of patients with 'scan-negative' CES dem- onstrating a pain, medication and functional mechanism of symptom production. ingrid.hoeritzauer@ed.ac.uk